Enhancing Critical Thinking Skills through The Development of Educational Kit Based on Problem Based Learning on Conservation Material - Hamimi*, Erti; Danissa, Fanny Putri; Affriyenni, Yessi (Universitas Syiah Kuala, 2024)
Critical thinking skills (CTS) are essential preparations for addressing challenges in the 21st century era. The use of traditional lecture learning models and less innovative media leads to student passivity and negatively impacts critical thinking levels. This study aims to develop a valid, practical, and effective educational Kit based on problem based learning (PBL) on conservation to enhance CTS. The research model employed is analyze, design, develop, implement, and evaluate. Data collection techniques included literature surveys, interviews, questionnaires, and tests. Qualitative data were acquired from interviews, comments form validators, as well as practical comments and suggestions from teachers and students. These were analyzed using qualitative descriptive analysis techniques. Additionally, quantitative data from content and media expert testing results, practicality assessments by teachers and students, as well as pretest and posttest scores, were analyzed using SPSS and percentage analysis techniques. The media validation yielded a result of 93.54%, and material validation achieved 94.78%, both falling within the very valid category. In the practical aspect involving teachers and students, the results reached 93.76%, demonstrating a high level of practicality in the applied learning criteria. The pretest and posttest results of the students revealed a discernible difference. The N-gain test, gauging the difference between the two, indicated a moderate improvement. The highest increase was observed in the inference indicator with a score of 0.67, while the self-regulation indicator showed the lowest improvement at 0.34. In conclusion, the educational Kit based on PBL was found to be valid, practical, and effective in enhancing CTS